Multiple Splenic Hamartomas in a Trauma Patient: Report and Literature Review of a Rare Entity. (28th October 2020) - Khokhar, H; Beversdorf, W; Jetly, R
Abstract: Introduction/Objective: The most common non-hematopoietic primary lesions of the spleen are benign and vascular in nature. Most are encountered incidentally at autopsy, trauma, or by imaging. The histologic differential diagnosis is challenging and often requires the use of immunohistochemical stains to distinguish from other aggressive lesions. We present a case of multiple splenic hamartomas discovered incidentally in a routine surgical specimen. Methods: A 46-year-old male trauma patient with no known medical history underwent splenectomy after sustaining a grade 3 splenic laceration. Results: The specimen weighed 198 grams and featured hemorrhagic capsular disruption. Within the intact parenchyma were multiple non-encapsulated, discrete pale foci ranging in size from 1–9 mm. Microscopically, these corresponded to multiple well-demarcated nodules with tortuous slit-like and dilated vascular channels lined by plump endothelial cells with no significant atypia or mitotic activity, and CD8 + /CD31 + /CD68 + (focal)/CD21 - /CD34 - phenotype by immunohistochemical staining. The intervening stroma was disorganized, with abundant foamy histiocytes and scattered lymphocytes with no defined white pulp-like structures. Histopathologic and immunohistochemical findings supported a diagnosis of splenic hamartomas. Conclusion: Exclusive to the spleen, splenic hamartomas are composed of mixed normal red and white pulp elements in disorganized configuration. They have no known demographic predilection and are exceedingly rare, with one institutional study reporting an incidence of 0.024–0.13% at autopsies. Congenital malformations of red pulp, neoplasms of red pulp, and post-traumatic reactive origin have been discussed as possible etiologies. Although rarely presenting with splenomegaly and hypersplenism, most cases are asymptomatic. Differentiation from other splenic vascular lesions is often challenging, and CD8 positivity in endothelial cells is usually a defining characteristic. Familiarity with the features of this rare and benign entity is important to distinguish it from malignant primary and metastatic tumors.